Clinical and microbiological studies of aminoglycosides efficiency in purulent inflammatory processes - Dmytriiev, D; Nazarchuk, O; Babina, Y; Maistruk, S (Annals of Mechnikov’s Institute, 2020)
Introduction. Infectious complications of diabetic foot syndrome are one of the main complications of diabetes mellitus, as well as a significant risk factor for amputation of the lower limb. The use of effective antimicrobial therapy is an important component in the treatment of these infections. Knowing the problem of antibiotic resistance in our time, the choice of starting antimicrobial drug is very important to reduce ineffective treatment, resistance to antibacterial agents, unwanted complications and economic costs. Objective. Conduct a comparative microbiological study of the antimicrobial efficacy of aminoglycosides against pathogens of wound suppurative-inflammatory processes and determine the clinical effectiveness of these agents. Materials and methods. The study included 45 patients with purulent-inflammatory processes of wounds in diabetic foot syndrome who received surgical treatment and antibiotic therapy. Patients were randomly assigned to three groups according to the prescription of antibiotics from the class of aminoglycosides (tobramycin, amikacin, gentamicin). Clinically took into account the general condition of the patients, wound healing, laboratory parameters (blood test, procalcitonin, CRP). Microbiological research was carried out in the bacteriological laboratory of the Department of Microbiology. Microbiological identification of the isolated microorganisms was carried out by the classical method according to morphological, tinctorial, cultural, biochemical features. Results & discussion. Microbiologically established polymicrobiality of wound contents in patients with diabetic foot Syndrome. Gram-positive and gram-negative microorganisms were identified. Aminoglycosides (gentamicin, tobramycin, amikacin) provide the same bacteriostatic, bactericidal effect on sensitive clinical strains of S. aureus, S. epidermidis, E. coli, E. cloacae, P. aeruginosa, K. teriggena, tobramycin had the advantage of antimicrobial activity to A baumannii, E. faecalis, and resistant strains of staphylococcus (p <0.05). As a result of studies, good tolerance by patients to antibiotics from the aminoglycoside group as starting monotherapy in 91.8% was revealed. according to A. baumannii, E. faecalis, and resistant staphylococcus strains (p <0.05). Clinically, tobramycin also showed advantages in local wound healing and, according to laboratory data (a decrease in the level of leukocytosis, procalcitonin and CRP), is 30% more effective in the first 6 days of antibiotic therapy, compared with group 2 and 3 of the study. Conclusion. Considering the polymicrobial spectrum of infectious pathogens in diabetic foot syndrome and the antibiotic resistance of the use of aminoglycosides in monotherapy for mild to moderate processes and in combination therapy with other antibiotics for severe degrees of complications, this is a balanced strategy for preventing the development of microbial resistance. Aminoglycosides (gentamicin, tobramycin, amikacin) provide both bacteriostatic and bactericidal effects on gram-positive and gram-negative pathogens, and especially tobramycin, which has the advantages of antimicrobial activity against A. baumannii, E. faecalis, and resistant strains of staphylococcus. DOI: 10.5281/zenodo.3885199